Development of an intelligent material handling equipment selection system: a review of recent research - Vasili, Mohammad Reza; Tang, Sai Hong (2005)
The most important task in the material handling system design process is the selection and configuration of equipment for material transport and storage in a facility. Material handling equipment selection is a complex, tedious task, and there are few tools other than checklists to assist engineers in the selection of appropriate, cost-effective material handling equipment. This paper reviews the development of an intelligent material handling equipment selection in open literature. The concept proposed in this paper can automate the design of a material handling equipment selection system, and provides artificial intelligence in the decision-making process.